COMP-trace effects in German: the role of processing - Schippers, Ankelien; Vogelzang, Margreet; Öwerdieck, David (Nordlyd, 2020)
This article reports on the processing and comprehension of COMP-trace violations in German. The status of the COMP-trace effect in German is a controversial issue. It has been argued that judgments on long-distance (LD) subject questions are distorted because of parsing problems in the main clause, the embedded clause, or both, and that LD subject questions are sometimes misinterpreted as object questions. Our self-paced reading data shows that processing difficulties with LD subject questions occur in the embedded clause, not the main clause, particularly at the point at which an embedded subject gap is postulated. Our study furthermore shows that readers are garden-pathed towards object readings of subject long-distance questions, but only when the embedded clause contains a case-ambiguous DP. A case-ambiguous DP thus functions as a superficial work-around for a COMP-trace violation. As we argue, our data support the view that German has a genuine COMP-trace effect and that potential parsing problems only occur in the context of local ambiguities. We propose that differences in the magnitude and fatality of COMP-trace violations between languages can be explained by formulating the COMP-trace effect in terms of accessibility, rather than a categorical syntactic constraint.
Keywords: COMP-trace effect; long-distance movement; self-paced reading; good-enough processing; garden-path effects; criterial freezing; anti-locality; accessibility hierachy; empty category principle